Household migration during a time of crisis: Patterns and outcomes in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
This study analyzes household migration, including paths, causes, challenges, and post-migration outcomes in Myanmar between February 2021 and July 2023 using the Myanmar Household Welfare Survey and the Myanmar Migration Assessment. During this period, we find that approximately ten percent of households in Myanmar migrated as a household or family unit. While nearly 40 percent of migration was urban-to-urban, a quarter was rural-to-rural, a quarter was rural-to-urban, and ten percent was urban-to-rural.